DIGITAL EDUCATION AT EUROPEAN HIGHER EDUCATION INSTITUTIONS DURING COVID-19 PANDEMIC - Kristina Feldvari; Sabina Rako; Milijana Mičunović (Vjesnik Bibliotekara Hrvatske, 2024)
Objective. The objective of this study was to identify and interpret state-of-the-play of the implementation of digital education (DE) in higher education institutions (HEIs) in the field of library and information science (LIS) during COVID-19 pandemic.